Hydrodynamics and water exchange in the Narta Lagoon, Albania - Scovenna, Mattia; De Leo, Francesco; Mucerino, Luigi; Crivellaro, Marta; Besio, Giovanni (Frontiers in Marine Science, 2025)
The Narta Lagoon, located along the Albanian coastline, is a unique and ecologically rich habitat supporting diverse bird and aquatic species, coastal dune ecosystems, and a valuable floral community. However, the lagoon is particularly vulnerable due to its limited connectivity with the Adriatic Sea, which occurs only through two narrow inlets whose opening is irregular and artificially managed. This restricted exchange, combined with increasing anthropogenic pressures, including planned tourism infrastructure and the presence of a nearby landfill, raises concerns about the lagoon’s environmental health. In this study, we investigate the lagoon’s hydrodynamic circulation and its capacity for water renewal using a combination of field observations and three-dimensional numerical modeling. Results reveal that water exchange is generally weak and predominantly driven by wind forcing, while tidal influence remains negligible. Under certain wind conditions, the lagoon exhibits prolonged stagnation, increasing the risk of water quality degradation and eutrophication. These findings highlight the lagoon’s limited resilience to external stressors and underscore the need for improved water management, regular monitoring, and targeted conservation strategies to safeguard this ecologically significant system.